Profil Kadar Asam Urat Pada Buruh Konveksi Bagian Penjahitan - Hawa Tirta Putri (Poltekkes Kemenkes Semarang, 2022)
Hyperuricemia can cause arthritis gout. One of the factors causing hyperuricemia is the inactivity of a person due to work. For example, workers who sew in clothing manufacturers generally sit for a long time. Other factors that can increase uric acid levels are age, sex, hereditary history, and consumption of high purine foods. Purpose of the study was to determine uric acid levels in garment manufacturers in the sewing section in Grenggeng Village, Kebumen Regency. The method is this study was observational descriptive with cross sectional approach. Examination of uric acid levels was carried out using Point Of Caring Test method. The results is subjects of the study were 30 garment manufacturing workers in the sewing section. There were 16 subjects who had normal uric acid levels (53%) and 14 subjects had uric acid levels above normal (47%). Uric acid levels above normal in the age group 50-60 years were 33.3%, in the age 40-49 years 10%, in the age 30-39 years 3.3%. Subjects who sit for a 8 hours/day were 63,3%, while who sit for 8 hours / day were 36,7%. Subjects who had above normal uric acid levels while sitting 8 hour/day were 16.7%, while those sitting 8 hours/day were 30%. Subjects with a history of hyperuricemia were 30%, and consumed high purine foods more than 5 times/week were 20%. Conclusion is 53% of factory workers who make sewing clothes have normal uric acid levels and 47% above normal levels.